Answer: 3
Step-by-step explanation: Simplifying
2(x + -3) + 9 = 3(x + -1) + x
Reorder the terms:
2(-3 + x) + 9 = 3(x + -1) + x
(-3 * 2 + x * 2) + 9 = 3(x + -1) + x
(-6 + 2x) + 9 = 3(x + -1) + x
Reorder the terms:
-6 + 9 + 2x = 3(x + -1) + x
Combine like terms: -6 + 9 = 3
3 + 2x = 3(x + -1) + x
Reorder the terms:
3 + 2x = 3(-1 + x) + x
3 + 2x = (-1 * 3 + x * 3) + x
3 + 2x = (-3 + 3x) + x
Combine like terms: 3x + x = 4x
3 + 2x = -3 + 4x
Solving
3 + 2x = -3 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
3 + 2x + -4x = -3 + 4x + -4x
Combine like terms: 2x + -4x = -2x
3 + -2x = -3 + 4x + -4x
Combine like terms: 4x + -4x = 0
3 + -2x = -3 + 0
3 + -2x = -3
Add '-3' to each side of the equation.
3 + -3 + -2x = -3 + -3
Combine like terms: 3 + -3 = 0
0 + -2x = -3 + -3
-2x = -3 + -3
Combine like terms: -3 + -3 = -6
-2x = -6
Divide each side by '-2'.
x = 3
Simplifying
x = 3